Do the Monetary Policy Makers Follow Rules? Testing Taylor’s Rule for Nepal (Economic Journal of Nepal, 2019)
The study estimates Taylor’s rule for Nepal by using the annual time series data for the period of 1988-2018. As a requirement of Taylor's rule, the output gap has been estimated by using Hodric-Perscott filter. Consumer price index has been used as measure of inflation and 91-days treasury bills rate is taken as the proxy for the short-term interest rate set by central bank of Nepal. The ordinary least square method has been used to estimate the Taylor's equation The results show that. As Augmented Dickey-Fuller test shows that all  the variables used in this study are in level form. The results show that there is a positive relationship of T-bills rule with inflation output gap. Interest rate smoothing is found to be a major concern of central bank of Nepal but follows the Taylor’s rule partially.